The vestibular system: a spatial reference for bodily self-consciousness - Pfeiffer, Christian; Serino, Andrea; Blanke, Olaf (Frontiers in Integrative Neuroscience, 2014)
Self-consciousness is the remarkable human experience of being a subject: the ‘I’. Self-consciousness is typically bound to a body, and particularly to the spatial dimensions of the body, as well as to its location and displacement in the gravitational field. Because the vestibular system codes head position in three-dimensional space, vestibular cortex is likely to contribute to spatial aspects of bodily self-consciousness. We review here recent data showing vestibular effects on first-person perspective (the feeling from where ‘I’ experience the world) and self-location (the feeling where ‘I’ am located in space). We compare these findings to data showing vestibular effects on mental spatial transformation, self-motion perception, and body representation that show that vestibular signals contribute to various spatial representations of the body with respect to the external world. Finally, we discuss four posterior brain regions that process vestibular and other multisensory signals to encode spatial aspects of bodily self-consciousness: temporoparietal junction (TPJ), parietoinsular vestibular cortex (PIVC), medial superior temporal region (MST), and ventral intraparietal region (VIP). We propose that vestibular processing in these cortical regions is important for linking multisensory signals from within personal space with those from extrapersonal space, and for spatial aspects of bodily self-consciousness.